A negative electrode material with artificial SEI and preparation method thereof

By pretreating graphite and forming artificial SEI, the problem of SEI failure of graphite negative electrode materials during charge and discharge cycles is solved, achieving more efficient electrochemical performance and more stable battery performance.

CN118630177BActive Publication Date: 2025-03-25HUNAN LINTE ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410820593.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-03-25
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

During the charge and discharge cycle, the continuous formation and peeling of SEI lead to capacity loss and lithium deposition, which reduces battery performance and increases safety risks. The existing artificial SEI is prone to failure or decomposition.

Method used

By pretreating graphite, emulsifying and dispersing, preoxidizing and dropping monomers and initiators, stable artificial SEI is formed to ensure its uniform coverage and stable structure.

Benefits of technology

The uniformity, stability and strength of the graphite surface SEI is achieved, and it is not easy to fail or decompose due to charge and discharge cycles, improving the first-time Coulomb efficiency and electrochemical performance of secondary ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118630177B_ABST
    Figure CN118630177B_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode material with artificial SEI and a preparation method thereof, comprising the following steps: calcining graphite at 300 to 700 degrees Celsius for 0.5 to 5 hours to obtain pretreated graphite; mixing the pretreated graphite with water and an emulsifier, stirring for 0.5 to 2 hours under an inert gas atmosphere and heating to 60 to 90 degrees Celsius to obtain an emulsion; adding an initiator to the emulsion, continuing the reaction for 0.5 to 2 hours to obtain a pre-oxidation liquid; simultaneously dropping a monomer and an initiator into the pre-oxidation liquid, reacting for 1 to 5 hours, and obtaining a negative electrode material with artificial SEI. The present invention ensures the uniform formation of SEI on the graphite surface through the preparation method of the above-mentioned entire process, and at the same time, the bonding force is strong, the structure is stable, and it will not fail or decompose due to charge and discharge cycles. When applied to the negative electrode material of a secondary ion battery, it can effectively improve the first coulomb efficiency and electrochemical performance, and the process is simple and controllable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material with artificial SEI and a preparation method thereof. Background Art

[0002] As one of the most important energy storage technologies in today's era, ion batteries play a vital role in the field of mobile electronic devices and electric vehicles. This battery technology is popular mainly due to its high energy density, long cycle life and relatively stable discharge characteristics. One of the core components of the battery is the negative electrode material, and graphite, as a traditional negative electrode material, occupies a core position in this field with its unique physical and chemical properties.

[0003] Although graphite anode is the main component of current energy storage batteries, the peeling of graphite sheets and the continuous formation of SEI during the charge and discharge cycle lead to serious capacity loss and lithium deposition, which reduces the performance of graphite-based batteries and increases safety risks. Surface modification, that is, the realization of artificial SEI on the graphite surface, is one of the most commonly used methods to enhance the long-term cyclability of graphite. However, artificial SEI is currently prone to failure or decomposition during charge and discharge cycles. Summary of the invention

[0004] Based on this, the present invention provides a method for preparing a negative electrode material with artificial SEI having good long-term stability.

[0005] A method for preparing a negative electrode material having an artificial SEI comprises the following steps:

[0006] calcining graphite at 300 to 700 degrees Celsius for 0.5 to 5 hours to obtain pretreated graphite;

[0007] The pretreated graphite is mixed with water and an emulsifier, stirred for 0.5 to 2 hours under an inert gas atmosphere, and then heated to 60 to 90 degrees Celsius to obtain an emulsion;

[0008] Adding an initiator to the emulsion and continuing the reaction for 0.5 to 2 hours to obtain a pre-oxidation solution;

[0009] Add the monomer and the initiator to the pre-oxidation solution simultaneously, and react for 1 to 5 hours to obtain a negative electrode material with an artificial SEI.

[0010] In one of the embodiments, the mass ratio of the emulsifier, pretreated graphite and water is 1:100:600.

[0011] In one embodiment, the initiator is selected from one or more of ammonium persulfate, potassium persulfate and hydrogen peroxide.

[0012] In one embodiment, when an initiator is added to the emulsion, the mass of the initiator is 2% to 8%, preferably 4.5%, of the pretreated graphite.

[0013] In one of the embodiments, when the monomer and the initiator are simultaneously added dropwise to the pre-oxidation solution, the mass ratio of the monomer, the initiator and the pre-treated graphite is 1-5:0.1-0.5:10, preferably 2.5:0.3:10.

[0014] In one embodiment, the dropping speed of the monomer and the initiator is 8-12 mL / h, preferably 10 mL / h.

[0015] In one embodiment, the monomer is selected from one or more of acrylic acid and methyl methacrylate.

[0016] In one embodiment, the emulsifier is selected from one or more of sodium lauryl sulfate, sodium stearate and sodium lauryl sulfonate.

[0017] In one embodiment, the method further comprises the following steps: filtering the product and drying it in a vacuum drying oven at 50 to 70 degrees Celsius for 8 to 15 hours.

[0018] The present invention also provides a negative electrode material, which is prepared according to the above preparation method.

[0019] The present invention also provides a secondary ion battery, which contains the negative electrode material.

[0020] In one embodiment, the secondary ion battery further contains a conductive agent and sodium carboxymethyl cellulose, and the mass ratio of the negative electrode material to the conductive agent and sodium carboxymethyl cellulose is 8:1:1.

[0021] The above solution of the present invention has the following beneficial effects:

[0022] The present invention first performs a specific pretreatment on graphite so that a large number of functional groups are formed on the graphite surface, so that artificial SEI can be better formed later; then emulsification dispersion is performed so that the graphite can be evenly dispersed; then pre-oxidation is performed so that the wet graphite has a valence bond with the artificial SEI, and the artificial SEI structure is more stable; then monomers and initiators are added dropwise so that the polymerization reaction on the monomer surface is uniform, and the artificial SEI coating is more uniform and stable. The present invention ensures the uniform formation of SEI on the graphite surface through the preparation method of the above-mentioned entire process, and at the same time, the bonding force is strong, the structure is stable, and it will not fail or decompose due to the charge and discharge cycle. When applied to the negative electrode material of a secondary ion battery, it can effectively improve the initial coulomb efficiency and electrochemical performance, and the process is simple and controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a transmission electron microscope image of the negative electrode material prepared in Example 1 of the present invention;

[0024] Figure 2 This is a transmission electron microscope image of the negative electrode material after the battery is cycled 100 times in Example 1 of the present invention;

[0025] Figure 3 This is a transmission electron microscope image of the graphite negative electrode material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The reagents and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods without specific conditions in the examples are implemented according to conventional conditions, such as the conditions described in the literature, books or methods recommended by the manufacturer.

[0028] Example 1

[0029] 1. Calcine the graphite at 500°C in a muffle furnace for 1.5 hours to obtain pretreated graphite;

[0030] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0031] 3. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0032] 4. Prepare solution A (2.5 g acrylic acid dissolved in 10 ml water) and solution B (0.3 g ammonium persulfate dissolved in 10 ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0033] 5. Filter the product obtained from the above reaction, and dry the obtained material in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material. Figure 1 Shown is a transmission electron microscope image of the prepared negative electrode material.

[0034] Use the above dry powder to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, add it to deionized water and stir it to make a slurry, apply it on copper foil, and dry it. The dried electrode pieces are cut into pieces and button cells are assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests are carried out to obtain electrochemical data, and the first coulomb efficiency is 84.01%. After 100 cycles, the battery is disassembled to take out the negative electrode material, such as Figure 2 Shown is a transmission electron microscope image of the negative electrode material after cycling, which shows that the negative electrode material is relatively stable.

[0035] Example 2

[0036] 1. Calcine the graphite at 500°C in a muffle furnace for 1.5 hours to obtain pretreated graphite;

[0037] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0038] 3. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0039] 4. Prepare solution A (1g acrylic acid dissolved in 10ml water) and solution B (0.3g ammonium persulfate dissolved in 10ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0040] 5. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0041] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests were carried out to obtain electrochemical data, and the first coulomb efficiency was 82.87%.

[0042] Since the amount of acrylic acid monomer is changed, the uniformity of the artificial SEI on the graphite surface is reduced, and the first coulombic efficiency is reduced compared with Example 1.

[0043] Example 3

[0044] 1. Calcine the graphite at 500°C in a muffle furnace for 1.5 hours to obtain pretreated graphite;

[0045] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 65 degrees.

[0046] 3. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0047] 4. Prepare solution A (1g acrylic acid dissolved in 10ml water) and solution B (0.3g ammonium persulfate dissolved in 10ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0048] 5. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0049] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests were carried out to obtain electrochemical data, and the first coulomb efficiency was 80.87%.

[0050] Since the reaction temperature was changed, the polymerization degree of the acrylic acid monomer was affected, thereby affecting the structure of the artificial SEI, and the first coulombic efficiency decreased compared with Example 2.

[0051] Example 4

[0052] 1. Calcine the graphite at 300°C in a muffle furnace for 1 hour to obtain pretreated graphite;

[0053] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0054] 3. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0055] 4. Prepare solution A (2.5 g acrylic acid dissolved in 10 ml water) and solution B (0.3 g ammonium persulfate dissolved in 10 ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0056] 5. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0057] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests were carried out to obtain electrochemical data, and the first coulomb efficiency was 80.21%.

[0058] Comparative Example 1

[0059] Directly configure the graphite button battery, such as Figure 3 The figure shows a transmission electron microscope image of a graphite negative electrode material. According to the mass ratio of graphite powder: conductive agent: CMC of 8:1:1, add it to deionized water and stir it to make a slurry, coat it on copper foil, and dry it. The dried pole piece is cut into pieces, and button cells are assembled in a glove box, with a lithium sheet as the counter electrode. At a current density of 36mA g-1, charge and discharge tests are carried out to obtain electrochemical data, and the first coulomb efficiency is 76.4%. Untreated graphite will produce irreversible capacity during the charge and discharge process due to the generation of SEI, resulting in a low first coulomb efficiency.

[0060] Comparative Example 2

[0061] 1. Take 10g of untreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0062] 2. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0063] 3. Prepare solution A (2.5 g acrylic acid dissolved in 10 ml water) and solution B (0.3 g ammonium persulfate dissolved in 10 ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0064] 4. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0065] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests were carried out to obtain electrochemical data, and the first coulomb efficiency was 80.07%.

[0066] Graphite that has not been pretreated has weak bonding strength with artificial SEI, which results in the inability to effectively play the role of artificial SEI and leads to a decrease in electrochemical performance.

[0067] Comparative Example 3

[0068] 1. Calcine the graphite at 500°C in a muffle furnace for 6 hours to obtain pretreated graphite;

[0069] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0070] 3. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0071] 4. Prepare solution A (2.5 g acrylic acid dissolved in 10 ml water) and solution B (0.3 g ammonium persulfate dissolved in 10 ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0072] 5. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0073] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests were carried out to obtain electrochemical data, and the first coulomb efficiency was 79.53%.

[0074] Due to the long pretreatment oxidation time, too many oxygen-containing functional groups are generated on the graphite surface, resulting in uneven artificial SEI on the graphite surface, which in turn leads to a decrease in electrochemical performance.

[0075] Comparative Example 4

[0076] 1. Calcine the graphite at 500°C in a muffle furnace for 1.5 hours to obtain pretreated graphite;

[0077] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0078] 3. Dissolve 0.45 g of ammonium persulfate in 4 ml of water, add to the solution in step 2, and react for 0.5 hour.

[0079] 4. Prepare solution A (6 g acrylic acid dissolved in 10 ml water) and solution B (0.3 g ammonium persulfate dissolved in 10 ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0080] 5. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0081] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with the counter electrode being a lithium sheet. At a current density of 36 mA g-1, charge and discharge tests were performed to obtain electrochemical data, and the first coulomb efficiency was 76.51%.

[0082] Due to the excessive amount of acrylic acid monomer, an artificial SEI with too large molecular weight will be produced, which is not conducive to ion transport and leads to a decrease in electrochemical performance.

[0083] Comparative Example 5

[0084] 1. Calcine the graphite at 500°C in a muffle furnace for 1.5 hours to obtain pretreated graphite;

[0085] 2. Take 10g of pretreated graphite and add it to 60ml of deionized water, then add 0.1g of sodium dodecyl sulfate, mix evenly for 30 minutes, stir while passing inert gas, and then heat to 85 degrees.

[0086] 3. Prepare solution A (2.5 g acrylic acid dissolved in 10 ml water) and solution B (0.3 g ammonium persulfate dissolved in 10 ml water). Add solution A and solution B to the solution in step 3 simultaneously for 1 hour, and continue the reaction for 2 hours.

[0087] 4. The product obtained from the above reaction was filtered and dried in a vacuum drying oven at 60 degrees Celsius for 10 hours to obtain a dry powder, i.e., the negative electrode material.

[0088] The above dry powder was used to configure the battery. According to the mass ratio of dry powder: conductive agent: CMC of 8:1:1, it was added to deionized water and stirred to make a slurry, coated on copper foil, and dried. The dried electrode was cut into pieces and button cells were assembled in a glove box, with lithium sheets as the counter electrode. At a current density of 36mA g-1, charge and discharge tests were carried out to obtain electrochemical data, and the first coulomb efficiency was 79.58%.

[0089] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material having an artificial SEI, characterized in that: The following steps are involved: calcining graphite at 300 to 700 degrees Celsius for 0.5 to 5 hours to obtain pretreated graphite; The pretreated graphite is mixed with water and an emulsifier, stirred for 0.5 to 2 hours under an inert gas atmosphere, and then heated to 60 to 90 degrees Celsius to obtain an emulsion; Adding an initiator to the emulsion and reacting for 0.5 to 2 hours to obtain a pre-oxidation solution; Add the monomer and the initiator to the pre-oxidation solution simultaneously, and continue the reaction for 1 to 5 hours to obtain a negative electrode material with an artificial SEI.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the emulsifier, pretreated graphite and water is 1:100:

600.

3. The preparation method according to claim 1, characterized in that: The initiator is selected from one or more of ammonium persulfate, potassium persulfate and hydrogen peroxide.

4. The preparation method according to claim 1, characterized in that: When an initiator is added to the emulsion, the mass of the initiator is 2% to 8% of the pretreated graphite.

5. The preparation method according to claim 1, characterized in that: When the monomer and the initiator are simultaneously added dropwise to the pre-oxidation solution, the mass ratio of the monomer, the initiator and the pre-treated graphite is 1-5:0.1-0.5:

10.

6. The preparation method according to claim 1, characterized in that: The monomer is selected from one or more of acrylic acid and methyl methacrylate.

7. The preparation method according to claim 1, characterized in that: The emulsifier is selected from one or more of sodium lauryl sulfate, sodium stearate and sodium lauryl sulfonate.

8. A negative electrode material, characterized in that Prepared according to the preparation method according to any one of claims 1 to 7.

9. A secondary ion battery, characterized in that: It contains the negative electrode material according to claim 8.

10. The secondary ion battery according to claim 9, characterized in that: It also contains a conductive agent and sodium carboxymethyl cellulose, and the mass ratio of the negative electrode material to the conductive agent and sodium carboxymethyl cellulose is 8:1:1.

Citation Information

Patent Citations

  • Modification method of natural graphite negative electrode material

    CN111960413A

  • Artificial graphite negative electrode material with SEI layer as well as preparation method and application of artificial graphite negative electrode material

    CN113964310A